CAPITAL FLOW, EXPORT GLOW: UNRAVELLING THE SYNERGY BETWEEN FOREIGN DIRECT INVESTMENT AND INDIA’S EXPORT PERFORMANCE - Agrawal, Sajal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Foreign Direct Investment (FDI) has become integral to India’s economic narrative since the 1991 liberalization reforms. This study delves into the captivating synergy between FDI and India’s export performance, a relationship often shrouded in complexity. Using the Autoregressive Distributed Lag (ARDL) model, the analysis employs time-series data from 1991 to 2023 to unravel the multifaceted impact of FDI on exports. The findings reveal that a 1% increase in FDI boosts exports by 0.18% in the long term and 0.09% in the short term, underscoring the significance of foreign capital in driving export growth. The study also highlights the importance of aligning FDI with export-oriented sectors through policy frameworks like the "Make in India" initiative. As the global economy navigates shifting trade paradigms and geopolitical realignments, understanding the intricate relationship between FDI and export performance becomes paramount. In conclusion, this research offers valuable insights into how India can leverage FDI for sustainable, export-led prosperity. By addressing structural challenges and fostering an investment-friendly environment, India can continue to climb the global value chain and cement its status as a premier destination for foreign capital. JEL Code: F10, F21, F40